Enhancing Thermal Properties of Co3O4 Nanoparticles Through Optimized Mn-Doping Concentrations - Girmaye Ambissa Begaw; Ababay Ketema Worku; Delele Worku Ayele; Temesgen Atnafu Yemata; Tessera Alemneh Wubieneh; Minbale Admas Teshager; Fantahun Aklog Yihun (International Journal of Electrochemistry)
Herein, a facile co-precipitation technique was employed to prepare cobalt oxide (Co3O4) and Co3O4 nanoparticles (NPs) with manganese (Mn) doping. The morphologies and crystalline structures of the as-prepared NPs were characterized by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), differential thermal analysis (DTA), thermogravimetric analysis (TGA), and Brunauer–Emmett–Teller (BET) techniques. XRD measurements showed that Co3O4 (19.42 nm) and Mn-doped Co3O4 (14.02 nm) NPs were successfully synthesized on average, and they exhibit a face-centered cubic crystalline structure. The SEM images also depicted the spherical morphology of Co3O4 NPs, with Mn particles clustering together. FTIR spectroscopy further confirmed the presence of Mn within the doped Co3O4 NPs. TGA/DTA analysis revealed boosted thermal stability in Mn-doped Co3O4 NPs compared to Co3O4 NPs. Moreover, the BET surface areas of Co3O4 and Mn-doped Co3O4 NPs were 534.013 and 712.741 m2/g, respectively, indicating an increase in surface area due to Mn doping. Consequently, Mn doping enhances both surface area and thermal stability, rendering Mn-doped Co3O4 NPs desirable for nanomaterial applications. This study shows that modulating the Mn doping concentration in the Co3O4 NPs offers superior surface area and thermal stability compared to the prepared Co3O4 NPs.